Influence of integrated nutrient management on growth, yield and quality of mustard (Brassica Juncea L.): Influence of integrated nutrient management on growth, yield and quality of mustard (Brassica Juncea L.) - SHARAD SHIKANDAR JADHAV; NIRANJAN R CHAVAN (Journal of Oilseeds Research, 2023)
A field experiment was conducted during rabi 2020- 2021 at Experimental Farm, Agronomy, Oilseeds Research Station with objectives of to study the influence of integrated nutrient management on growth, yield and quality of mustard. The experiment was laid out in Randomized Block Design with 8 treatments each with three replications. The results of the experiment indicated that combined application of RDF + Vermicompost @ 2.5 t/ha (T3) observed significantly maximum growth parameters, dry matter, yield attributes and yield. The application of RDF + Vermicompost @ 2.5 t/ha (T3) recorded the significantly highest oil content. The application of RDF + Vermicompost @ 2.5 t/ha (T3) obtained maximum net returns. Highest B:C ratio was obtained with the application of RDF + Vermicompost @ 2.5 t/ha (T3).